2021
DOI: 10.1038/s41598-021-83898-3
|View full text |Cite
|
Sign up to set email alerts
|

Cortical oscillations that underlie visual selective attention are abnormal in adolescents with cerebral palsy

Abstract: Adolescence is a critical period for the development and refinement of several higher-level cognitive functions, including visual selective attention. Clinically, it has been noted that adolescents with cerebral palsy (CP) may have deficits in selectively attending to objects within their visual field. This study aimed to evaluate the neural oscillatory activity in the ventral attention network while adolescents with CP performed a visual selective attention task. Adolescents with CP (N = 14; Age = 15.7 ± 4 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…In fact, when we pooled the studies that applied matching, only a medium-sized effect was found for inhibitory control; however, the large effect on working memory remained. Additionally, similar effects were found for verbal [26,27,31,34,36] and visuospatial working memory [26][27][28][29]31,32,[35][36][37][38][39], and for measures of shifting [26,29,31,36,37,39] and planning [26,36]. In sum, we confirmed the results of previous studies [13][14][15][16] showing substantial deficits in EF skills in CP.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In fact, when we pooled the studies that applied matching, only a medium-sized effect was found for inhibitory control; however, the large effect on working memory remained. Additionally, similar effects were found for verbal [26,27,31,34,36] and visuospatial working memory [26][27][28][29]31,32,[35][36][37][38][39], and for measures of shifting [26,29,31,36,37,39] and planning [26,36]. In sum, we confirmed the results of previous studies [13][14][15][16] showing substantial deficits in EF skills in CP.…”
Section: Discussionsupporting
confidence: 90%
“…We found strong agreement between reviewers in selecting studies based on full texts (Cohen's kappa = 0.92). The characteristics of the included studies are shown in Table 1 [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. * GMFCS: Mild = at least 80% of the CP participants belong to GMFCS level I, II, III according to the article.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…divided attention in active condition), nor group differences in attention (i.e. reduced attention function in CP) (Hoffman et al., 2021; VerMaas et al., 2020). As opposed to attention, it is more probable that the attenuation of the somatosensory cortical responses was dependent on efferent signals induced by a motor command inhibiting the sensory afferent signals, a mechanism referred to as centrifugal gating or central gating (Jones et al., 1989; Wasaka et al., 2003; Saradjian, 2015).…”
Section: Discussionmentioning
confidence: 99%